Engineering of large cartilaginous constructs through the use of microchanneled hydrogels and rotational culture - Kelly, Daniel; Buckley, Conor (My University, 2009)
The development of functional engineered cartilaginous tissues of sufficient size that can be used clinically to treat large defects remains a major and significant challenge. This study investigated if the introduction of microchannels into chondrocyte-seeded agarose hydrogels would result in the formation of a superior and more homogenous cartilaginous tissue due to enhanced nutrient transport. Microchannel construct cylinders were fabricated via a moulding process utilising a pillared structure to create the required architecture. Constructs were subjected to either constant rotation in a rotational bioreactor system or free swelling conditions. After 28 days of free swelling culture the presence of microchannels did not enhance GAG accumulation within the core of the construct compared to solid constructs (0.317 ? 0.002 % w/w vs. 0.401 ? 0.020 % w/w). However under dynamically rotating conditions, GAG accumulation in the cores (1.165 ? 0.132 % w/w) of microchannel constructs were similar to that in the periphery (1.23 ? 0.074 % w/w) of solid constructs, although still significantly lower than their corresponding periphery (1.64 ? 0.133 % w/w) after 28 days. These results confirm that cellular nutrient consumption is primarily responsible for creating the spatial gradients in molecules regulating the biosynthetic activity of chondrocytes through the volume of hydrogels, and that changing the scaffold architecture alone may have little effect while the inherent diffusivity of the material remains high. Rather a combination of forced convection and modified scaffold architecture is necessary to engineer large cartilaginous tissues in vitro.
PUBLISHED
PMID: 19374490
Keywords: Bioengineering; Cartilage repair; Next Generation Medical Devices